2010
DOI: 10.2139/ssrn.1562602
|View full text |Cite
|
Sign up to set email alerts
|

Test of Okun’s Law in Some Asian Countries Co-Integration Approach

Abstract: The objective of this paper is to estimate the Okun's coefficient, and to check the validity of Okun's law in some Asian countries whether it is valid or not, for this purpose we have used the time series annual data during the period 1980. Engle Granger (1987 co integration technique is employed to find out long run association between variables and error correction mechanism (ECM) is used for short run dynamic. After getting empirical evidences it can be said that Okun's law interpretation may not be applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 18 publications
3
25
0
1
Order By: Relevance
“…Though the long run coefficient is just 0.7 % higher than the hypothesised, the positive sign invalidates Okun's claim. The findings are in accordance with Lal et al (2010) and likewise Kreishan (2011) and other researches on the subject. However, the ECM is negative as expected implying that for the system of unemployment rates in SA to be reinstated back to normal, a short run adjustment rate of about 12.8 % per quarter may be applied.…”
Section: Resultssupporting
confidence: 92%
“…Though the long run coefficient is just 0.7 % higher than the hypothesised, the positive sign invalidates Okun's claim. The findings are in accordance with Lal et al (2010) and likewise Kreishan (2011) and other researches on the subject. However, the ECM is negative as expected implying that for the system of unemployment rates in SA to be reinstated back to normal, a short run adjustment rate of about 12.8 % per quarter may be applied.…”
Section: Resultssupporting
confidence: 92%
“…Lal et al [19] estimated and tested the Okun's law in some Asian countries using data from 1980 to 2006. Employing the Engle granger cointegration test and the error correction model, the study found the okun's law not to hold for some Asian countries.…”
Section: Andrei Andmentioning
confidence: 99%
“…Whereas the country's labour force grew at an average rate of 0.3% every year, the GDP growth rate at 1984 factor cost grew at 3.5% over a period of 33 years. In the same vein, the Okun's coefficient was studied in order to validate the law in some Asian countries using the annual time series data between 1980 and 2006 (Lal, 2010). In addition, the research employed the Error Correction Mechanism (ECM) evaluate the dynamics in the short run.…”
Section: Literature and Empirical Reviewsmentioning
confidence: 99%